EVALUASI MOTIVASI KERJA GURU RUMPUN PENDIDIKAN AGAMA ISLAM MAN MANNA KABUPATEN BENGKULU SELATAN - susna yulisti (UIN Fatmawati Sukarno Bengkulu, 2018)
ABSTRACT: The results of this research show that teachers’ work motivation Islamic Education clump of Islamic Religious Education (PAI) in MAN Manna South Bengkulu, Learning and how the working conditions of teachers of Islamic education, between the theoretical concept and reality. Implementation of supervision in the field of learning, the reality is far from ideal concept. The cause is so complex, ranging from understanding the context of supervision itself is not owned by the actors, both supervisors, principals, and teachers of Islamic education. To overcome this gap, socialization and “pressure” from those who are committed to the quality of education in Indonesia. It is jointly have to do with the development of a culture of quality in education, which in essence is the quality of the learning process in the classroom. Factors affecting work motivation of teachers of Islamic education clump of Islamic Religious Education (PAI) in MAN Manna South Bengkulu, personal / individual, include knowledge, skills (skills), ability, self-confidence, motivation, and commitment of every individual, leadership factors, including: the quality in providing impetus, encouragement, guidance and support of the manager and the team leader, a factor the team, include: the quality of support and encouragement given by a colleague in a team, trust in his fellow team members, compactness and closeness member team, system factors, including: the working system, working facilities or infrastructure provided by colleagues as a team, trust in his fellow team members, compactness and the closeness of the team members.